To solve this equation using PEMDAS (Order of Operations), follow these steps:
1. Begin by simplifying the expression inside the parentheses:
-8(-3n + 5) = 24n - 40
2. Rewrite the equation with the simplified expression:
-90 = 24n - 40 - 2
3. Simplify the right side by combining like terms:
-90 = 24n - 42
4. Move the constant term (-42) to the left side by adding 42 to both sides:
-90 + 42 = 24n - 42 + 42
-48 = 24n
5. Divide both sides by 24 to isolate "n":
-48/24 = 24n/24
-2 = n
Therefore, the solution is n = -2.
-90 = -8(-3n+5) - 2
solve using pemdas
1 answer